Analisis Kemampuan Representasi Matematis Siswa Dalam Memahami Materi Sistem Persamaan Linear Dua Variabel - Lala Intan Komalasari (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
The purpose of this study was to analyze the mathematical representation ability of eighth grade students of SMP Negeri 02 Woja in understanding the material for the Two-variable Linear Equation System. The method used in this research is descriptive method. The descriptive method uses descriptive statistics to process the data obtained from the research results. In addition, the researchers conducted interviews with mathematics teachers who directly taught class VIII students in order to strengthen the data obtained in addition to tests. The findings of this study are as follows: The overall mathematical representation ability of students has an average score of 59.87; The ability of mathematical representation on the pictorial representation has an average of 50.98. The ability of mathematical representation on the symbol representation indicator has an average of 65.66. Mathematical representation ability on verbal representation indicators has an average of 62.45.